“No One Sends You Flowers”: Social Norms and Patients’ Emotional Journey Within Fertility Treatment - Böcker, Julia; Jakoby, Nina (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Patients undergoing fertility treatment, such as IVF, experience a range of emotions—hope, disappointment, grief, anxiety, jealousy, guilt, and anger. Through a sociology of emotions lens, we trace the emotional journey of patients in fertility treatment in Switzerland to understand subjects’ experiences with medically assisted reproduction (MAR), and to highlight how societal and cultural norms and expectations shape the way they use and emotionally manage (failed) fertility treatments. The theoretical background is grounded in the notion of feeling rules (Hochschild, 1983) and associated concepts such as disenfranchised grief (Doka, 2002). Methodologically, the article is based on a qualitative interview study conducted with affected women in Switzerland (LoMAR) and a quantitative analysis of the first wave of CHARLS, a nationwide longitudinal study. Linking qualitative and quantitative data allows us to show the significance of occurring emotions as well as a deeper understanding of particularly strong emotions felt during (failed) treatment cycles that the research participants have disclosed in the interviews. Further, we argue that fertility treatment itself contributes to producing what we call “layers of loss,” a cumulation of multiple losses experienced.
Keywords: Infertility; IVF; Medically Assisted Reproduction; Narrative Interviews; Reproductive loss; Emotion; 618 Gynäkologie, Geburtsmedizin, Pädiatrie, Geriatrie; 614 Inzidenz und Prävention von Krankheiten